Silverlight and ASP.NET Revealed - MacDonald, Matthew; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2007)
Microsoft Silverlight allows you to create rich multimedia interfaces with the power and flexibility of Flash, but with the extensibility and the great tools that .NET offers. With Silverlight and ASP.NET Revealed, you'll learn to use Microsoft's Silverlight technology in conjunction with ASP.NET and Visual Studio 2008 (code name Orcas). You will ultimately incorporate Silverlight into an ASP.NET web site and use the ASP.NET controls that render Silverlight content. You'll get the basics of Silverlight, too, making this book a must–read for any web developer curious about Silverlight.
Keywords: Microsoft software; Microsoft .NET Framework; Software engineering; Microsoft and .NET.; Software Engineering/Programming and Operating Systems